Ala/Ala Genotype of Pro12Ala Polymorphism in the Peroxisome Proliferator-Activated Receptor-γ2 Gene Is Associated with Obesity and Insulin Resistance in Asian Indians - Bhatt, Surya Prakash (Mary Ann Liebert, Inc., 2012)
AIM: We determined the association of the Pro12Ala polymorphism of the peroxisome proliferator activated receptor (PPAR)-γ2 gene with obesity, insulin resistance (IR), and lipids in Asian Indians without diabetes in north India. SUBJECTS AND METHODS: In this cross-sectional study (n=495; 279 males and 216 females, 18–60 years of age), anthropometric (body mass index, waist and hip circumferences, and skinfold thickness) and biochemical (fasting glucose, lipid profile, fasting insulin, leptin, and adiponectin) parameters were assessed. Polymerase chain reaction–restriction fragment length polymorphism analysis was used for identification of individual genotypes. RESULTS: Frequencies of the Pro and Ala alleles were 0.89 and 0.11, respectively. The genotype frequencies (%) of Pro/Pro, Pro/Ala, and Ala/Ala were 82.6, 14.7, and 2.7, respectively, without any gender differences. The frequency of the Ala/Ala genotype was higher in obese than in nonobese subjects (4.9% vs. 1.5%, P=0.06). The Ala/Ala genotype was associated with higher values of hip circumference, subscapular skinfold thickness, and sum of four skinfold thickness than the Pro/Pro and Pro/Ala genotypes (P<0.05). Using a multivariate logistic regression model after adjusting for age, sex, and insulin, subjects with the Ala/Ala genotype showed a high risk of obesity (odds ratio [OR], 3.2, 95% confidence interval [CI] 1.2–12.9) and IR (OR, 3.6, 95% CI: 1.04–12.4). CONCLUSION: The Ala/Ala genotype of the PPAR-γ2 gene is associated with obesity and IR in Asian Indians without diabetes living in north India.